A KNOX-Cytokinin Regulatory Module Predates the Origin of Indeterminate Vascular Plants - Coudert, Yoan; Novák, Ondřej; Harrison, C Jill (Current biology, 2019)
The diverse forms of today's dominant vascular plant flora are generated by the sustained proliferative activity of sporophyte meristems at plants' shoot and root tips, a trait known as indeterminacy [1]. Bryophyte sister lineages to the vascular plants lack such indeterminate meristems and have an overall sporophyte form comprising a single small axis that ceases growth in the formation of a reproductive sporangium [1]. Genetic mechanisms regulating indeterminacy are well characterized in flowering plants, involving a feedback loop between class I KNOX genes and cytokinin [2, 3], and class I KNOX expression is a conserved feature of vascular plant meristems [4]. The transition from determinate growth to indeterminacy during evolution was a pre-requisite to vascular plant diversification, but mechanisms enabling the innovation of indeterminacy are unknown [5]. Here, we show that class I KNOX gene activity is necessary and sufficient for axis extension from an intercalary region of determinate moss shoots. As in Arabidopsis, class I KNOX activity can promote cytokinin biosynthesis by an ISOPENTENYL TRANSFERASE gene, PpIPT3. PpIPT3 promotes axis extension, and PpIPT3 and exogenously applied cytokinin can partially compensate for loss of class I KNOX function. By outgroup comparison, the results suggest that a pre-existing KNOX-cytokinin regulatory module was recruited into vascular plant shoot meristems during evolution to promote indeterminacy, thereby enabling the radiation of vascular plant shoot forms.
Keywords: ISOPENTENYL TRANSFERASE; cytokininy; KNOX-cytokinin; indeterminacy; Homeodomain Proteins; molekulární evoluce; mechy; biologická evoluce; Evolution, Molecular; evo-devo; plant evolution; Biological Evolution; homeodoménové proteiny; vascular plant origins; Plant Proteins; Bryopsida; rostlinné proteiny; Cytokinins